Manual de los Reglamentos del Agua de Florida: Agencias de Contacto - Michael T. Olexa; Laura Minton; Dulcy Miller; Sarah Caldwell (EDIS)
Este es el documento EDIS FE090, una publicación del Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publicada Noviembre 2002.